2022
DOI: 10.1186/s12974-021-02370-1
|View full text |Cite
|
Sign up to set email alerts
|

Immune response and pathogen invasion at the choroid plexus in the onset of cerebral toxoplasmosis

Abstract: Background Toxoplasma gondii (T. gondii) is a highly successful parasite being able to cross all biological barriers of the body, finally reaching the central nervous system (CNS). Previous studies have highlighted the critical involvement of the blood–brain barrier (BBB) during T. gondii invasion and development of subsequent neuroinflammation. Still, the potential contribution of the choroid plexus (CP), the main structure forming the blood–cerebrospinal fluid (CSF) barrier (BCSFB) have not b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 96 publications
1
9
0
Order By: Relevance
“…Thus, the CP tissue contained a higher relative foci density compared with the parenchymal and meningeal tissues and the vasculature. Interestingly, recent work reported that T. gondii infection of the CP entailed inflammatory responses and impaired B-CSF barrier function [43]. Jointly, this indicates that the CP constitutes a locus of passage by T. gondii, as shown for T. brucei [37,40].…”
Section: Passage Of T Gondii Across the Cp Meninges And Blood-retina ...mentioning
confidence: 95%
“…Thus, the CP tissue contained a higher relative foci density compared with the parenchymal and meningeal tissues and the vasculature. Interestingly, recent work reported that T. gondii infection of the CP entailed inflammatory responses and impaired B-CSF barrier function [43]. Jointly, this indicates that the CP constitutes a locus of passage by T. gondii, as shown for T. brucei [37,40].…”
Section: Passage Of T Gondii Across the Cp Meninges And Blood-retina ...mentioning
confidence: 95%
“…injection of cysts of the type II ME49 strain, previously harvested from brains of female NMRI mice infected i.p. with T. gondii cysts 6–12 months before, as described elsewhere [ 51 ]. Briefly, brains isolated from NMRI mice were mechanically homogenized in 1 ml sterile phosphate-buffered saline (PBS), and the number of cysts was determined in ≥ 80 µl homogenate using a bright field microscope.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous work, ICAM-1 and VCAM-1 were described to be expressed exclusively in epithelial cells of the choroid plexus [ 129 ]. However, recent single cell analysis reported the expression of ICAM-1 and VCAM-1 transcripts in subclustered choroid plexus endothelial cells [ 120 , 135 ]. The presence of ICAM-1 and VCAM-1 adhesion molecules in the endothelium of the choroid plexus suggests a new role of the PVB in the immune modulation of the CNS.…”
Section: The Immunoregulatory Function Of the Choroid Plexusmentioning
confidence: 99%